Evaluasi dan Perancangan Model Bisnis Usulan Fibo School Menggunakan Business Model Canvas - Adawiyah, Grannisa Nurul; Hasun, Farda; Pulungan, Muhammad Almaududi (Metode : Jurnal Teknik Industri, 2025)
Fibo School is a learning management system product based on Artificial Intelligence technology. Since its launch until now, the number of users of Fibo School products is still very low. The root causes of the low number of users are human resources, products, promotions, and processes and partnerships. One way to overcome these problems is to evaluate and design a proposed business model using the Business Model Canvas. The required data are existing business model data, customer profile data, and business environment data. Evaluation of the existing business model is done by analyzing 7 questions and SWOT analysis to get a proposed strategy. Some of the proposed improvements are focusing its market segmentation to private educational institutions in West Java Province and Special Region of Jakarta, creating materials and learner evaluations according to the curriculum, providing a variety of subscription packages, and building partnerships to help product development and marketing. In addition, a financial simulation was conducted to calculate the financial impact of the proposed business model changes. If an increase of 25 customers can be obtained in the first year after the implementation of the proposed business model, with a 20% increase in sales in the following year, then the business model change will provide an IRR value greater than the MARR of 11.30% and an NPV value greater than zero.